2020
DOI: 10.2151/jmsj.2020-049
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Lidar Water Vapour Mixing Ratio and Temperature Profiles into a Convection-Permitting Model

Abstract: The impact of assimilating thermodynamic profiles measured with lidars into the Weather Research and Forecasting (WRF)-Noah-Multiparameterization model system on a 2.5-km convection-permitting scale was investigated. We implemented a new forward operator for direct assimilation of the water vapor mixing ratio (WVMR). Data from two lidar systems of the University of Hohenheim were used: the water vapor differential absorption lidar (UHOH WVDIAL) and the temperature rotational Raman lidar (UHOH TRL). Six experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 94 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…One month of ground-based Raman Lidar data and airborne lidar observations from approximately 20 flights were used in the reanalyses conducted by Fourrié et al (2015Fourrié et al ( , 2019Fourrié et al ( , 2021). • Thundathil et al (2020) assimilated even both water vapor and temperature lidar data into the weather and research Forecast model on the convection-permitting scale applying a 3D-Var rapid update cycle and found that especially the assimilation of moisture results in a significant improvement of the model fields.…”
Section: Challenges Objectives and Strategymentioning
confidence: 99%
“…One month of ground-based Raman Lidar data and airborne lidar observations from approximately 20 flights were used in the reanalyses conducted by Fourrié et al (2015Fourrié et al ( , 2019Fourrié et al ( , 2021). • Thundathil et al (2020) assimilated even both water vapor and temperature lidar data into the weather and research Forecast model on the convection-permitting scale applying a 3D-Var rapid update cycle and found that especially the assimilation of moisture results in a significant improvement of the model fields.…”
Section: Challenges Objectives and Strategymentioning
confidence: 99%
“…The assimilation of temperature and moisture profiles obtained from active remote‐sensing lidar systems (e.g. Wulfmeyer et al ., 2015) offers great potential for improving the predictive skills of NWP models (Wulfmeyer et al ., 2006; 2015; Adam et al ., 2016; Leuenberger et al ., 2020; Thundathil et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to a strong increase of road traffic in major European cities (Thunis et al, 2017), pollution limits are often violated in larger cities. For example, for particulate matter with particle diameters less than 10 µm (PM 10 ), the critical value is an annual mean concentration of 20 µg m −3 or a daily mean value of 50 µg m −3 (WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%